Petualangan Energi Angin Bersama Anak Rumah Singgah - Erwani Merry Sartika; Meilan Jimmy Hasugian; Markus Tanubrata; Novie Theresia Br. Pasaribu; Herawati YS; Arvin Ezekiel Denri Utama; Dido Hardinanto Ginting; Jeffrey Christopher; Yehuda Njuah Sectio Cibro (Jurnal Atma Inovasia, 2026)
The wind energy adventure with children from the shelter home has become the focus of a community service initiative aimed at elementary school children in the Cibogo area. The need for alternative forms of learning to stimulate interest and engagement among children at the shelter inspired the application of science using a wind power car as the central theme of this community service program. The activity was conducted using an experimental method, training the children to observe, design tools, measure results, and draw conclusions from the objects they created—ranging from mechanical components to the drive system—through hands-on experimentation. The outcomes of this wind energy adventure had a positive impact on the children, the service team, and the surrounding community, fostering awareness of the importance of experiment-based education and providing valuable knowledge to all participants involved.